Four-Hand Piano transcriptions and reception of symphonic repertoire in nineteenth-century Europe - Miller-Kay, Elissa (Universiti Pendidikan Sultan Idris, 2018)
Four-Hand Piano transcriptions and reception of symphonic repertoire in nineteenth-century Europe by Miller-Kay, Elissa